Distribution of archaeological sites of Ancient Peru is linked to climatology and natural vegetation. - Galán-de-Mera, A.G. (2020)
In this article, we try to discover a parallelism among climate and bioclimate belts, use of the territory, and previously studied plant communities, taking into account historical and archaeological data to find an answer as to how different cultures perceived the landscapes. After a statistical analysis generating a Sørensen dendrogram, we were able to observe how archaeological sites were ordered according to bioclimatic belts, crops, and human activity; the results of a canonical correspondence analysis (CCA) showed connections among archaeological sites, crops, products, and plant associations of the landscapes. Groups with the most humid climate represent areas with crops with a seasonal rain regime and shepherding of llamas and alpacas, while groups with the driest climate represent areas whose crops need irrigation. Notably, occidental slope areas with cactus associations present a terrace agricultural system irrigated by water springs, while sites near riparian plant associations are joined to vegetable gardens. Amazonian and Oriental Andean crops are present in the same bioclimatic belt in comparison to the coast. Using a minimal spanning tree (MST), hypothetical roads to exchange products between different crop areas could be traced with a high coincidence with the Inca Road (Qhapaq Ñan).